Post‐mortem analysis on the analysis and evaluation of risks in construction project management - Schieg, Martin (Journal of Business Economics and Management, 2007)
Risk management is used more and more in building industry projects. An essential element of the risk management process is the analysis and evaluation of risks. Therefore, project assessment with the help of the post‐mortem analysis plays an important role. The post‐mortem analysis is a tool frequently used in software projects today for the reduction of risks. The clearness of the goal of improvement measures is sharpened by the examination of the project steps in connection with the success factors of the organization. The results of a post‐mortem analysis deliver detailed information on where improvement measurements are necessary in the project future. Growth in project management know‐how is created through the discussion of the participants of all hierarchy levels. Therefore, the post‐mortem analysis is also applicable for use in the construction project. The procedure is introduced in the work at hand.First Published Online: 14 Oct 2010